Chronic Pain and Associated Factors in India and Nepal: A Pilot Study of the Vanderbilt Global Pain Survey. (November 2017) - Walters, Jenna L.; Baxter, Kelly; Chapman, Hannah; Jackson, Tracy; Sethuramachandran, Adinarayanan; Couldridge, Marcus; Joshi, Hem Raj; Kundra, Pankaj; Liu, Xulei; Nair, Divya; Sullivan, Bonnie; Shotwell, Matthew S.; et al.
Abstract : BACKGROUND: Evaluation and treatment of chronic pain worldwide are limited by the lack of standardized assessment tools incorporating consistent definitions of pain chronicity and specific queries of known social and psychological risk factors for chronic pain. The Vanderbilt Global Pain Survey (VGPS) was developed as a tool to address these concerns, specifically in the low- and middle-income countries where global burden is highest. METHODS: The VGPS was developed using standardized and cross-culturally validated metrics, including the Brief Pain Inventory and World Health Organization Disability Assessment Scale, as well as the Pain Catastrophizing Scale, the Fibromyalgia Survey Questionnaire along with queries about pain attitudes to assess the prevalence of chronic pain and disability along with its psychosocial and emotional associations. The VGPS was piloted in both Nepal and India over a 1-month period in 2014, allowing for evaluation of this tool in 2 distinctly diverse cultures. RESULTS: Prevalence of chronic pain in Nepal and India was consistent with published data. The Nepali cohort displayed a pain point prevalence of 48%–50% along with some form of disability present in approximately one third of the past 30 days. Additionally, 11% of Nepalis recorded pain in 2 somatic sites and 39% of those surveyed documented a history of a traumatic event. In the Indian cohort, pain point prevalence was approximately 24% to 41% based on the question phrasing, and any form of disability was present in 6 of the last 30 days. Of the Indians surveyed, 11% reported pain in 2 somatic sites, with only 4% reporting a previous traumatic event. Overall, Nepal had significantly higher chronic pain prevalence, symptom severity, widespread pain, and self-reported previous traumatic events, yet lower reported pain severity. CONCLUSIONS: Our findings confirm prevalent chronic pain, while revealing pertinent cultural differences and survey limitations that will inform future assessment strategies. Specific areas for improvement identified in this VGPS pilot study included survey translation methodology, redundancy of embedded metrics and cultural limitations in representative sampling and in detecting the prevalence of mental health illness, catastrophizing behavior, and previous traumatic events. International expert consensus is needed. Abstract : Supplemental Digital Content is available in the text.Published ahead of print August 10, 2017.